PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI PT BANK DANAMON BANDUNG TIMUR - Miharja, Shandy Aditia; Ruhkviyanti, Novi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study investigates the impact of transformational leadership style and work motivation on employee performance at PT Bank Danamon Bandung Timur. The quantitative method was used by distributing 1–5 Likert scale questionnaires to 62 permanent employees. Data analysis used SPSS version 27 with the classical assumption test, multiple linear regression, F test, t test, correlation coefficient, and determination. The results show that transformational leadership style has no significant influence on employee performance, while work motivation has a positive and significant influence. However, simultaneously, transformational leadership style and work motivation have a positive and significant impact on employee performance. The results of this study emphasize the importance of strong work motivation factors in improving employee performance in the banking environment.